Body and Boat: Significance of Morphology on Elite Rowing Performance - De Larochelambert, Quentin; Del Vecchio, Scott; Leroy, Arthur; Duncombe, Stephanie; Toussaint, Jean-Francois; Sedeaud, Adrien (Frontiers in Sports and Active Living, 2020)
Objectives: The purpose of this study was to determine and weigh the anthropometric indicators that were associated with pacing performances for each Olympic rowing category. Methods: Between 2010 and 2015, 1,148 rowers (650 men and 498 women) participated in the finals of World Championships in each heavyweight Olympic event. They were categorized into four morphological clusters according to their heigh and body mass index (BMI): tall and thin (TT), tall and robust (TR), small and thin (ST) and small and robust (SR). Time and speed, were collected every 50 meters for all boats in each competition. Non-parametric inferential methods were used to understand the differences in performance between morphological clusters over the entire race. After, we calculated a new indicator to determine the differences between these morphotypes within the race. Results: In this article, we determined which morphologies had a significant effect on speed for both men and women. For example, the biggest rowers were the fastest in skiff. Analysis of each 50 meters demonstrated that between the four morphological categories that the TR male athletes were significantly faster than their ST counterparts between the 800 and 2000 meters of the race by 1.76% of mean speed. Furthermore, the SR were the fastest in female coxless pairs over the majority of the race. These differences in speed by morphological cluster are summarized, by race segment, for all categories and sex. Conclusion: Anthropometric factors impact pacing among rowers’ categories. Coupling anthropometry and race pacing is not only helpful to understand which factors work where, but is also helpful in improving training and performance. This can help both in the recruiting of rowers for specific boats and adapting the race strategy. In future, the method used can be adapted for factors other than anthropometry. It can also be individualized to enable athletes to prepare for their race according to future competitors.